ANALYSIS OF BORAX AND FORMALDEHYDE CONTENT IN MEATBALLS IN AMBON CITY - Male, Yusthinus T; Rumakat, Dewi H; Fransina, Eirene G; Wattimury, Jusuf (Pattimura University, 2020)
A research has been done to analyze the content of borax and formalin content in several meatball sales places in Ambon City. This study uses two stages of analysis; qualitative analysis to determine the presence or absence of borax and formalin in meatballs and quantitative analysis to determine what levels of borax and formalin in meatballs. The results of the qualitative analysis of borax and formalin in the meatballs of ten samples showed one sample containing borax, which is sample A (Wayame) with borax content of 1.02% (w / w) while all of the samples sample did not contain formalin. Even though it is found in quite low levels, the use of borax as a food additive is not allowed because it is very dangerous for human health.